PENGEMBANGAN SILABUS PENDIDIKAN AGAMA ISLAM (PAI) UNTUK MENINGKATKAN PEMAHAMAN GURU TERHADAP KOMPETENSI SISWA - Juni Erpida Nasution (Al-Ihda' : Jurnal Pendidikan dan Pemikiran, 2018)
Government of Indonesia has decided educational unit curriculum as an operational curriculum which can be played up by every unit of education. It is played up in contain standard, curriculum component, curriculum structure, competence standard, educational calender, syllabus, teaching plan and so on. Especially, syllabus must be formulated by a teacher through teachers’ cooperation of lessons in certain school.